FACTORS CONTRIBUTING TO SEPTIC ABORTION AMONG WOMEN AGED 15-45 YEARS ATTENDING POSTNATAL CLINIC AT IRAN-UGANDA HOSPITAL, KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY. - Winfred Nanambi; Hasifa Nasereko (Student's Journal of Health Research, 2023)
Background: Septic abortion is an infection of the placenta and fetus, products of conception, of a pre-viable pregnancy. The purpose of the study was to examine the Factors contributing to septic abortion among women aged 15-45 years attending at IRAN-Uganda Hospital, Kampala district. Methodology: A descriptive cross-sectional research design was used to describe factors contributing to septic abortion among women aged 15-45 years attending at IRAN-Uganda Hospital. A cross-sectional descriptive study design was adopted in this study that involved observation of a sample of a population or phenomena that are made at one point in time. 30 respondents were involved in the study who were selected using convenient random sampling procedures. Results: (43.3%) of the women were aged 20-30 years, the majority of them (83.3%) were Catholics, half of them (50.0%) had never been to school, Majority (46.7%) of them were single. The majority of the respondents (46.7%) were employed, (93.3%) of them reported that the distance from home to the nearest health facility contributed to septic abortion, the majority (66.7%) reported unavailability of healthcare services being part of the factors leading to septic abortion,(56.7%)reported high cost of safe abortion services, (70%) reported that Poor attitude of health workers whereas (86.7%) said long- waiting-time, majority (66.7%) reported that unnecessary requirement like parent's or spouse consent before providing abortion services led to septic abortion Conclusion: Personal factors, socio-economic factors, and health facility-related factors contributed to septic abortions among the respondents hence advocacy is needed to improve and prevent septic abortions among women. Recommendation; Septic abortion among women can be reduced and managed by considering and maintaining a balance between regular health education talks about the dangers of septic abortion and all categories of abortions, and mass sensitization of the community against practices of septic abortion.